2010
DOI: 10.3892/or_00000854
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms in the DNA repair genes XPD and XRCC1, p53 gene mutations and bladder cancer risk

Abstract: Abstract. Previous studies have suggested that certain genetic polymorphisms, specifically the Xeroderma pigmentosum group D (XPD) gene codon 751 and the X-ray repair crosscomplementing group 1 (XRCC1) gene codon 399 polymorphisms, were associated with an increased risk of lung cancer, and, in some studies, with a greater risk for mutations in the p53 tumor suppressor gene in lung tumors. To evaluate whether these gene polymorphisms may be associated with an increased risk for bladder cancer or in association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Our observation of no association of the XPD Lys751Gln genotypes with the risk of Bladder cancer is compatible with the findings from Shen et al [ 13 ] and Gangwar et al [ 30 ] who reported no association of the ERCC2 codon 751 polymorphism with bladder cancer risk. However, Gao et al[ 16 ] and Li et al [ 17 ] suggest that individuals who have the ERCC2 751Gln allele may be at an increased risk for bladder cancer. Authors explain this association by the fact that ERCC2 gene mutations can diminish the activity of TFIIH complexes giving rise to repair defects, transcription defects, and abnormal responses to apoptosis [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our observation of no association of the XPD Lys751Gln genotypes with the risk of Bladder cancer is compatible with the findings from Shen et al [ 13 ] and Gangwar et al [ 30 ] who reported no association of the ERCC2 codon 751 polymorphism with bladder cancer risk. However, Gao et al[ 16 ] and Li et al [ 17 ] suggest that individuals who have the ERCC2 751Gln allele may be at an increased risk for bladder cancer. Authors explain this association by the fact that ERCC2 gene mutations can diminish the activity of TFIIH complexes giving rise to repair defects, transcription defects, and abnormal responses to apoptosis [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In X-ray repair cross-complementing protein 1 (XRCC1), rs1799782 and rs25489 are widely associated with an increased risk for BC, especially in Asian and Indian populations [146][147][148][149][150][151][152]. Rs915927 in the same gene increases tumor susceptibility in the Italian population [153] while rs25487 gave contradictory results in different studies [147][148][149][154][155][156][157][158][159]. Rs3218373, rs3218536, and rs6464268 in XRCC2 present a protective effect towards BC in the Italian population [160].…”
Section: Dna Repairmentioning
confidence: 99%
“…The XPD protein, an essential subunit of the transcription factor IIH (TFIIH) complex, unwinds DNA in damaged regions [22]. An XPD variant at position 751 in exon 23 (at position 35931 on exon 23, base A to C, rs13181) causing a lysine-to-glutamine transition has been associated with non-small cell lung cancer [23], breast cancer [24], bladder cancer [25], and colorectal cancer [26]. However, several studies failed to identify an increased PCa risk with XPD Lys751Gln polymorphism, namely in the Indian population [27], the Taiwanese population [28], and the South Australian population [29].…”
Section: Introductionmentioning
confidence: 99%